Experimental evidence that clay inhibits bacterial decomposers: Implications for preservation of organic fossils - McMahon, S; Anderson, R; Saupe, E; Briggs, D (Geological Society of America, 2016)
Exceptionally preserved organic fossils are commonly associated with clay-rich horizons or directly with clay minerals. It has been posited that interactions between clay minerals and organic tissues inhibit enzymatic reactions or protect carcasses in such a way that decay is impeded. However, interactions between clay minerals and the biological agents of decay, especially bacteria, may be at least as important to preservation potential. Here we show that clays of particle size <2 μmm in suspensions exceeding 10 mg/ml in concentration inhibit the growth of Pseudoalteromonas luteoviolacea, a marine heterotrophic bacterium involved in the decay of marine animals. Such clay-microbe interactions can contribute to exceptional preservation, and specific examples may play a role in shaping the distribution of Konservat- Lagerstätten through time.